PELATIHAN INOVASI DAN PENGEMBANGAN PRODUK PATERA ECO PRINT PALEMBANG - Husni Mubarat; Heri Iswandi; Muhsin Ilhaq (Universitas Muhammadiyah Mataram, 2021)
ABSTRAKPatera Eco Print sebagai mitra sasaran dalam implementasi program Pengabdian Kepada Masyarakat (PKM) yang bergerak di bidang ekonomi produktif memiliki beberapa permasalahan, yaitu belum adanya inovasi produk dan pengembangan desain baik dari segi eksplorasi bentuk, pengembangan jenis produk, maupun eksplorasi pola-pola motif daun yang ditata pada media kain tersebut. Adapun solusi yang ditawarkan sebagai pemecahan permasalahan tersebut, diantaranya adalah inovasi produk Patera Eco Print, pengembangan desain dan jenis-jenis produk. Adapun tujuan utama dari kegiatan ini adalah memberikan ilmu pengetahuan keterampilan tentang cara pengembangan desain produk ecoprint, seperti totebag dan tas laptop. Metode yang digunakan pada Pengabdian ini diantaranya adalah metode survei, dokumentasi, wawancara, pelatihan, sosialisasi dan evaluasi. Adapun capaian dari kegiatan ini yakni diharapkan mitra pelatihan ini dapat mengembangkan desain produk usaha Eco Print, seperti pengembangan desain totebag, tas laptop dan baju dengan demikian capaian ini dapat memperluas jangkauan pasar produk Patera Eco Print. Kata kunci: patera eco print; desain produk; inovasi. ABSTRACTPatera Eco Print as a target partner in the implementation of the Community Service program (PKM) which is engaged in the productive economy has several problems, namely the absence of product innovation and design development both in terms of exploration of forms, development of product types, and exploration of leaf motif patterns. which is arranged on the cloth media. The solutions offered to solve these problems include product innovation Patera Eco Print, design development and product types. The main purpose of this activity is to provide knowledge of skills on how to develop ecoprint product designs, such as tote bags and laptop bags. The methods used in this Community Service include survey methods, documentation, interviews, training, socialization and evaluation. The product output that will be achieved is to create innovative products, such as the development of designs for clothes, jackets and invitation bags, especially in the composition of the motives. The achievement of this activity is that it is hoped that this training partner can develop the design of Eco Print business products. In addition, the product output that will be achieved is the development of product types, such as laptop bags, tote bags, and shirts, such as the development of tote bag designs, laptop bags and clothes, thus this achievement can expand the market reach of Patera Eco Print products..Keywords: patera eco print; product design; innovation.